Evaluation of the Clinical Use of Ceftriaxone among In-Patients in Selected Health Facilities in Uganda - Paul Kutyabami; Edson Ireeta Munanura; Rajab Kalidi; Sulah Balikuna; Margaret Ndagire; Bruhan Kaggwa; Winnie Nambatya; Pakoyo Fadhiru Kamba; Allan Musiimenta; Diana Nakitto Kesi; Victoria Nambasa; Allan Serwanga; et al. (Antibiotics, 2021)
Ceftriaxone has a high propensity for misuse because of its high rate of utilization. In this study, we aimed at assessing the appropriateness of the clinical utilization of ceftriaxone in nine health facilities in Uganda. Using the World Health Organization (WHO) Drug Use Evaluation indicators, we reviewed a systematic sample of 885 patients’ treatment records selected over a three (3)-month period. Our results showed that prescriptions were written mostly by medical officers at 53.3% (470/882). Ceftriaxone was prescribed mainly for surgical prophylaxis at 25.3% (154/609), respiratory tract infections at 17% (104/609), and sepsis at 11% (67/609), as well as for non-recommended indications such as malaria at 7% (43/609) and anemia at 8% (49/609). Ceftriaxone was mostly prescribed once daily (92.3%; 817/885), as a 2 g dose (50.1%; 443/885), and for 5 days (41%; 363/885). The average score of inappropriate use of ceftriaxone in the eight indicators was 32.1%. Only 58.3% (516/885) of the ceftriaxone doses prescribed were administered to completion. Complete blood count and culture and sensitivity testing rates were 38.8% (343/885) and 1.13% (10/885), respectively. Over 85.4% (756/885) of the patients improved and were discharged. Factors associated with appropriate ceftriaxone use were gender, pregnancy status, days of hospitalization, health facility level of care, health facility type, and type of prescriber.